Beyond Legacy Systems: Assessing the Impact of a New-Generation Academic Information System on User Satisfaction in Higher Education - Iwan Suhandi; Arenawati; Titi Stiawati (Indonesian Journal of Social Science Research, 2025)
Digital transformation is a necessity for universities to improve their competitiveness and legitimacy. This study aims to examine the effect of implementing the New Generations Academic Information System (SIAKANG) on user satisfaction at Sultan Ageng Tirtayasa University. Using an explanatory quantitative approach and SEM-PLS analysis of 379 respondents, the results of the study prove that SIAKANG has a positive and very significant effect on user satisfaction. This is indicated by a path coefficient of 0.975 and an R-square value of 0.95, which means that SIAKANG is able to explain 95% of the variation in satisfaction. This system has succeeded in improving the efficiency of academic services for students, lecturers, and educational staff. This study reinforces DeLone & McLean's Information System Success Model and provides justification for information technology investment in higher education. Strategic recommendations include strengthening governance, developing system capacity, and optimising user-oriented features.